PRAKTIK SHARIA COMPLIANCE DI LEMBAGA KEUANGAN SYARIAH (STUDI KASUS PT. BANK MUAMALAT INDONESIA, TBK. KCP KOLAKA). - Indah Tutfiansyah; Nur Rahmah; Rahmat Mansur (Jurnal Syariah Hukum Islam, 2020)
Sharia banking is an effort to develop Islamic banks and takes into account that the majority of Muslims in Indonesia are waiting for a sound and reliable Islamic banking system that is in accordance with sharia principles. and there is a need for sharia compliance as a differentiator between Islamic banks and conventional banks. The DSN-MUI fatwa is a guideline for Islamic banks in order to maintain sharia compliance with the principles established by Islamic law. The formulation of the problem in this research is how the practice of sharia compliance on wadi'ah products at PT. Bank Muamalat KCP Kolaka? and What are the challenges and obstacles in the practice of sharia compliance on wadi'ah products at PT. Bank Muamalat KCP Kolaka? The purpose of this study was to determine the practice of sharia compliance on wadi'ah products at PT. Bank Muamalat KCP Kolaka and to find out the challenges and obstacles in the practice of sharia compliance on wadi'ah products at PT. Bank Muamalat KCP Kolaka. The research method used is a type of qualitative research with a descriptive approach with the aim of knowing the Sharia Compliance Practices in Islamic financial institutions (case study of PT. Bank Muamalat Indonesia, Tbk. KCP Kolaka). The data sources are managers, employees, customers as primary data, and Bank Muamalat KCP Kolaka documents as secondary data using interview and documentation data collection techniques. The collected data were analyzed to give conclusions. The results of this study can be concluded that the practice of sharia compliance on wadi'ah products uses the wadi'ah yad dhamanah contract type. In Sharia Compliance, its presence is one of the differences between Conventional Banks and Sharia Banks, as well as being one of the factors in advancing Islamic banks in creating innovations in wadi'ah products. Sharia Compliance is also based on two free indicators. Second MAGRHRIB, Fatwa DSN-MUI No. 02 / DSN-MUI.IV / 2000 Regarding general terms of savings based on the wadi'ah contract. Wadi'ah products at PT. Bank Muamalat Indonesia, Tbk. KCP Kolaka, the challenge for the general public regarding Islamic banking is that it needs socialization and wide dissemination to the community. Meanwhile, the obstacles in the practice of sharia compliance (sharia compliance) do not at all have obstacles because the mechanisms that are implemented are appropriate and follow Islamic Sharia and that is what keeps the Financial Institution in progress.